Fitobentos associados a bancos de rodolitos do Litoral Norte da Bahia: aspectos taxonômicos e ecológicos - Alves, Gérson Limoeiro (2012)
Rhodolith beds are one of the most important benthic communities in the Brazilian continental shelf, mainly which provides a three-dimensional structure that transforms homogeneous backgrounds and unconsolidated sediments on hard substrates and heterogeneous, thus expanding the available niches and allowing an increase of diversity of associated species. This study aimed to characterize the floristic composition and community structure of phytobenthic associated to rhodoliths beds in an area of the northern coast of Bahia. Analysis of the phytobenthic community structure consisted of total number of taxa identified, dry biomass (g / m²) and sedimentological composition of collection points, and statistical analysis of results collected at each point. Composition of the phytobenthic flora of the study area was predominantly tropical, being collected and identified 66 taxa of algae associated with rodolith, 17 Chlorophyta, 14 Heterokontophyta-class Phaeophyceae and 35 Rhodophyta. Bryopsiales (Chlorophyta), Dictyotales (Heterokontophyta) and Ceramiales (Rhodophyta) were the most representative orders. Four forms of growth of non-geniculate coralline algae were identified: warty, lumpy, encrusting and fruticose, and four types of rodoliths morphologies: spherical, cylindrical, laminar and discoid. Lithothamnion brasiliense Foslie and L. superpositum Foslie were identified as the main species forming the rhodoliths beds. The composition of the sedimentology was classified as sandy-gravelly biodetrical during the dry season, and gravel-sandy biodetrical during the rainy season. There were also differences in biomass values between the dry and rainy seasons, and the dry season possessed a higher biomass concentration than that observed in the rainy season. The results obtained for the values of Shannon diversity index (H ') and Pielou's evenness (J) corroborated the distinction observed between the dry and rainy season, thus revealing the existence of a pattern of seasonality in place.